An analysis of the benefit of using HEV genotype 3 antigens in detecting anti-HEV IgG in a European population. - Annatina Schnegg (Public Library of Science (PLoS), 2013)
Background The benefit of using serological assays based on HEV genotype 3 in industrialised settings is unclear. We compared the performance of serological kits based on antigens from different HEV genotypes. Methods Taking 20 serum samples from patients in southwest France with acute HEV infection (positive PCR for HEV genotype 3) and 550 anonymised samples from blood donors in southwest Switzerland, we tested for anti-HEV IgG using three enzyme immunoassays (EIAs) (MP Diagnostics, Dia.Pro and Fortress) based on genotype 1 and 2 antigens, and one immunodot assay (Mikrogen Diagnostik recomLine HEV IgG/IgM) based on genotype 1 and 3 antigens. Results All acute HEV samples and 124/550 blood donor samples were positive with ≥1 assay. Of PCR-confirmed patient samples, 45%, 65%, 95% and 55% were positive with MP Diagnostics, Dia.Pro, Fortress and recomLine, respectively. Of blood donor samples positive with ≥1 assay, 120/124 (97%), were positive with Fortress, 19/124 (15%) were positive with all EIAs and 51/124 (41%) were positive with recomLine. Of 11/20 patient samples positive with recomLine, stronger reactivity for HEV genotype 3 was observed in 1/11(9%), and equal reactivity for both genotypes in 5/11 (45.5%). Conclusions Although recomLine contains HEV genotype 3, it has lower sensitivity than Fortress in acute HEV infection and fails to identify infection as being due to this genotype in approximately 45% of patients. In our single blood donor population, we observe wide variations in measured seroprevalence, from 4.2% to 21.8%, depending on the assay used.